Evolutionary Game Analysis of Integration Decisions for Informal WEEE Processing Channels under Government Intervention - Zhang, Ziyan; Lei, Xue (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
The rapid growth of waste electrical and electronic equipment (WEEE) has become an important environmental issue. China’s WEEE recycling and treatment system consists of both formal and informal channels. Informal channels have long played an important role, but they are associated with serious pollution, low efficiency, and disorderly development. Based on China’s dual-channel recycling governance context, this study examines the integration strategy choices of upstream informal recyclers and downstream informal dismantlers under government support. First, this study constructs payoff matrices under different strategy combinations based on a Stackelberg game. It then applies evolutionary game theory to analyze the strategy evolution process of both parties and uses MATLAB simulations to examine the effects of key parameters. The results show that the behavioral evolution of informal participants exhibits a follow-the-other effect; that is, both parties tend to choose either “integration” or “non-integration” simultaneously. Government subsidies significantly affect the direction of equilibrium evolution. When the subsidies satisfy S1∈(0,0.97) and S2∈(0,1.93）, the system may evolve toward either “non-integration, non-integration” or “integration, integration” as stable states. When the subsidies exceed these ranges, the system is more likely to evolve toward “integration, integration. Numerical simulations further show that the recycling competition rate has a U-shaped effect on integration strategy choice. In addition, the lower the recycling utilization rate of informal dismantlers and the stronger the cooperation willingness of informal participants, the more likely the system is to evolve toward “integration, integration.”